The Diagnostic Utility of Combination of HMGA2 and IMP3 qRT-PCR Testing in Thyroid Neoplasms. Issue 1 (January 2015) - Jin, Long; Lloyd, Ricardo V.; Henry, Michael R.; Erickson, Lori A.; Sebo, Thomas J.; Rumilla, Kandelaria M.; Zhang, Jun
<x xml:space="preserve">Abstract</x> The diagnosis of malignant thyroid tumors in some cytologic and histologic specimens remains challenging. High-mobility group A2 (HMGA2) expression and insulin-like growth factor II mRNA-binding protein-3 (IMP3) expression were evaluated by relative quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The aim of this study was to evaluate whether the combination of HMGA2 and IMP3 qRT-PCR was diagnostically useful in differentiating benign from malignant thyroid neoplasms. Fine-needle aspiration (FNA) specimens from 120 patients including 56 benign lesions and 64 carcinomas were used. The available 80 corresponding formalin-fixed paraffin-embedded (FFPE) thyroid tissues from 66 patients were also included in this study. HMGA2 and IMP3 expression levels were detected by qRT-PCR and reported as relative fold change after normalizing with a calibrator. The diagnostic utilities of HMGA2 and IMP3 qRT-PCR tests were evaluated individually and in combination. In FNA specimens, HMGA2 and IMP3 expression was consistently higher in thyroid malignancies compared with benign lesions in all subgroups except in Hürthle cell tumors. After exclusion of Hürthle cell tumors, the sensitivity was 90.2% for HMGA2, 88.2% for IMP3, and 98% for HMGA2+IMP3; the specificity was 97.1% for HMGA2, 79.4% for IMP3, and 79.4% for HMGA+IMP3. qRT-PCR data showed similar results in FFPE tissues: the sensitivity was 84.2% for HMGA2, 85.7% for IMP3, and 94.7% for HMGA2+IMP3; the specificity was 96.9% for HMGA2, 91.2% for IMP3, and 90.6% for HMGA2+IMP3. qRT-PCR data were concordant between FNA and FFPE samples for HMGA2 (97.4%) and IMP3 (96.9%). The results indicate that HMGA2 qRT-PCR with high specificity may be a useful ancillary technique to assist in the classification of difficult thyroid specimens, excluding Hürthle cell tumors. The HMGA2 and IMP3 qRT-PCR combination model with increased sensitivity and negative predictive value (96.4%) may be useful in screening thyroid cytology specimens.